New Varieties of Coffee: Compromising the Qualities of Adaptive Agroforestry? A Case Study From Southern Mexico - Ruiz-de-Oña, Celia; Merlín-Uribe, Yair (Frontiers in Sustainable Food Systems, 2021)
The most recent wave of coffee leaf rust, and its interaction with climatic variability, caused severe crop losses in shade-grown coffee areas in Latin America during the 2010-14 pro-duction cycles and beyond. Fungal attack on traditional Arabica varieties led to a process of substitution with new coffee varieties that are tolerant or resistant to the pathogen. The ad-aptation literature classifies this type of intervention as an incremental adaptation, with the potential to lead the system towards sustainable transformation. This research explores the initial consequences of introducing certain hybrid varieties into the transboundary area of the Tacaná Volcano, located between Chiapas and Guatemala, with the objective of identi-fying aspects that put the potential for adaptive agroforestry at risk. We hypothesize that the interaction of a range of economic, political, and ecological factors leads to ambiguous results in terms of both production and environmental adaptation. Ecological and manage-ment variables were analysed in a case study of 30 producers. Quantitative data, collected through ecological plot sampling and application of a socio-productive survey, was com-plemented with ethnographic data. We conclude that, for our case study, the manner in which these new coffee varieties were introduced raises new sources of vulnerability that could be compromising the local and ecological benefits of agroforestry systems, as well as diminishing their capacity to cope with the future impacts of climate change.